2013
DOI: 10.1292/jvms.12-0424
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey to Determine the Occurrence of Malignant Catarrhal Fever Infection in the Japanese Small Ruminant Population from Northern Districts

Abstract: ABSTRACT. Ovine herpesvirus 2 (OvHV-2) causes sheep-associated malignant catarrhal fever (SA-MCF), and is responsible for economic losses in cattle and other susceptible species around the world. A survey of 154 serum samples from 14 flocks in 3 Japanese prefectures (Hokkaido, Aomori and Iwate) was undertaken between 2007 and 2008 to test for antibodies to OvHV-2. OvHV-2 was present in 56 sheep and 2 goats, with 37.66% of samples having a positive reaction using a serum neutralization test. The immune reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(29 reference statements)
0
2
0
1
Order By: Relevance
“…Anti-AlHV-1 neutralizing Abs have been consistently detected in animals in the Alcelaphinae and Hippotraginae subfamilies [ 11 , 17 ]. Sheep serum, however, has been reported to contain low to no AlHV-1 neutralizing activity [ 17 , 18 , 19 ] other than one study which reported neutralizing titers as high as 256 [ 20 ]. In that study 154 sheep sera were tested for neutralizing antibodies against the WC11 strain of AlHV-1; titers ≥ 4 (range 4–256) were reported as positive.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-AlHV-1 neutralizing Abs have been consistently detected in animals in the Alcelaphinae and Hippotraginae subfamilies [ 11 , 17 ]. Sheep serum, however, has been reported to contain low to no AlHV-1 neutralizing activity [ 17 , 18 , 19 ] other than one study which reported neutralizing titers as high as 256 [ 20 ]. In that study 154 sheep sera were tested for neutralizing antibodies against the WC11 strain of AlHV-1; titers ≥ 4 (range 4–256) were reported as positive.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, that, the most infections occur by close contact between the carrier animals and susceptible host (26). Several authors reported the transmission of OHV-2 has been occurred when cattle have been separated at least 70 m to5 km from a lamb (26,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…A epidemiologia da FCM ainda não é completamente esclarecida (Russell et al 2009, O´Toole & Li 2014, porém os casos são frequentemente vinculados à criação consorciada entre bovinos e ovinos portadores do OvHV-2 (Li et al 2001, Russell et al 2009) e, eventualmente, onde a criação é exclusivamente de bovinos (Furlan et al 2012). No Brasil, pouco se conhece quanto à prevalência da infecção pelo OvHV-2 em rebanhos ovinos e há escassos estudos no mundo (Li et al 1995, Mirangi & Kang'ee 1997, Wani et al 2006, Cortez et al 2008, Loken et al 2009, Bremer 2010, Giangaspero et al 2013.…”
Section: Introductionunclassified